Serial Measurements of Splanchnic Vein Diameters in Rats Using High-Frequency Ultrasound - Seitz, Bridget M.; Krieger-Burke, Teresa; Fink, Gregory D.; Watts, Stephanie W. (Frontiers in Pharmacology, 2016)
The purpose of this study was to investigate serial ultrasound imaging in rats as a fully non-invasive method to 1) quantify the diameters of splanchnic veins in real time as an indirect surrogate for the capacitance function of those veins, and 2) assess the effects of drugs on venous dimensions. A 21 MHz probe was used on anesthetized male Sprague-Dawley rats to collect images containing the portal vein (PV), superior mesenteric vein (SMV), abdominal inferior vena cava (IVC), and splenic vein (SpV; used as a landmark in timed studies) and the abdominal aorta (AA). Stable landmarks were established that allowed reproducible quantification of cross-sectional diameters within an animal. The average diameters of vessels measured every 5 minutes over 45 minutes remained within 0.75±0.15% (PV), 0.2±0.09% (SMV), 0.5±0.12% (IVC) and 0.38±0.06% (AA) of baseline (PV: 2.0±0.12 mm; SMV: 1.7±0.04 mm; IVC: 3.2±0.1 mm; AA: 2.3±0.14 mm). The maximal effects of the vasodilator sodium nitroprusside (SNP; 2 mg/kg, i.v. bolus) on venous diameters were determined 5 minutes post SNP bolus; the diameters of all noted veins were significantly increased by sodium nitroprusside, while mean arterial pressure decreased 29±4 mmHg. By contrast, administration of the venoconstrictor sarafotoxin (S6c; 5 ng/kg, i.v. bolus) significantly decreased PV and SpV, but not IVC, SMV or AA, diameters 5 minutes post S6c bolus; mean arterial pressure increased by 6±2 mmHg. In order to determine if resting splanchnic vein diameters were stable over much longer periods of time, vessel diameters were measured every two weeks for 8 weeks. Measurements were found to be highly reproducible within animals over this time period. Finally, to evaluate the utility of vein imaging in a chronic condition, images were acquired from 4-week deoxycorticosterone acetate salt (DOCA-salt) hypertensive and normotensive (SHAM) control rats. All vessel diameters increased from baseline while mean arterial pressure increased (67±4 mmHg) in DOCA-salt rats compared to SHAM at 4 weeks after pellet implantation. Vessel diameters remained unchanged in SHAM animals. Together, these results support serial ultrasound imaging as a non-invasive, reliable technique able to measure acute and chronic changes in the diameter of splanchnic veins in intact rats